The Simple Game of the Learning Model Approach on Elementary School Students - Muhammad Syam’un Al Ghazi; Kholid (Journal of English Education and Teaching, 2023)
This study aims to produce a product model of learning devices through a simple game to improve the speed and agility of upper grade of elementary school students, as well as determine the feasibility and effectiveness of learning device models through simple games.This learning device model was developed to be used by upper grade elementary school students, during PJOK learning, so that upper grade elementary school students are able to maintain speed and agility performance during PJOK learning. The method used in this research is a research and development method ( Research and Development) the Borg & Gall model which reviews problems, data collection, product design, design validation, design revisions, product trials, product revisions, usage trials, product revisions, and dissemination. The subjects of this study were PJOK teachers and elementary school students. The trials carried out included two stages, namely small-scale trials conducted on one PJOK teacher with 20 students, large-scale trials with two PJOK teachers with 40 students, and an effectiveness test with two PJOK teachers with 40 students. Based on the findings of the data and analysis, the researcher describes several parts of the findings through the validation assessment of material experts, obtaining an average rating of 3.83 in the "good/decent" category, validation by media experts obtaining a rating of 4.1 in the "good/decent" category. "good/decent", and the validation of Indonesian language experts received an assessment of 3.9 in the "good/decent" category, at the small-scale trial stage, the teacher's assessment results were obtained at 4.2 in the "very feasible" category and the test results speed and agility by 60% and 50% in the "enough" category, at the large-scale trial stage, the teacher's assessment results were obtained by 4.3 in the "very decent" category and the speed and agility test results were 75% and 65% with category "worthy". Based on the effectiveness test of the speed variable with the 40 m sprint test, the pretest value was 5.5% and the posttest was 90%. The agility variable with zig-zag running (IIlinois Aglitiy Test) obtained a pretest value of 47.5% and a posttest of 82.5%. It can be concluded that producing a learning device model through a simple game that has been validated for its feasibility and tested for its effectiveness in increasing the speed and agility of upper grade elementary school students. Keywords: Simple Game, Speed, Agility